EKSPLORASI DAN KARAKTERISASI BAKTERI RHIZOBIUM ASAL TANAMAN Mucuna bracteata DI TANAH GAMBUT - Isna Rahma Dini; Wawan Wawan Wawan; Hapsoh Hapsoh Hapsoh; Rahma Devi (Jurnal Agroekoteknologi, 2020)
The efficiency of fertilizing N on oil palm plants on peatlands in several companies isdone by planting legume cover crop, one of which is Mucuna bracteata. This plantcan form root nodules because it can symbiosis with rhizobium bacteria which willmake fixation of N2 in the air so that the bound N elements can be utilized by plants. This bacterium grows naturally on legume cover crop. This study aims to explore and characterize adaptive rhizobium bacteria in peatlands. The location of sampling is done at PT. Jatimjaya Perkasa, Kubu District, Rokan Hilir Regency. Sampling of root nodules by stratified random sampling. The results obtained by eight bacterial isolates that have relatively similar macroscopic and microscopic characteristics and belong to rhizobium based on the YEMA + CR and YEMA + BTB tests.Keywords: Peat soil, Oil palm, Legume cover crop, Rhizobium